Concurrent dinoprostone and oxytocin for labor induction in term premature rupture of membranes a randomized controlled trial - Tan, P.C. (2009)
OBJECTIVE: To estimate the effect of concurrent vaginal dinoprostone and oxytocin infusion against oxytocin infusion for labor induction in premature rupture of membranes (PROM) on vaginal delivery within 12 hours and patient satisfaction. METHODS: Nulliparas with uncomplicated PROM at term, a Bishop score less than or equal to 6, and who required labor induction were recruited for a double-blind randomized trial. Participants were randomly assigned to 3-mg dinoprostone pessary and oxytocin infusion or placebo and oxytocin infusion. A cardiotocogram was performed before induction and maintained to delivery. Dinoprostone pessary or placebo was placed in the posterior vaginal fornix. Oxytocin intravenous infusion was commenced at 2 milliunits/min and doubled every 30 minutes to a maximum of 32 milliunits/min. Oxytocin infusion rate was titrated to achieve four contractions every 10 minutes. Primary outcomes were vaginal delivery within 12 hours and maternal satisfaction with the birth process using a visual analog scale WAS) from 0 to 10 (higher score, greater satisfaction). RESULTS: One hundred fourteen women were available for analysis. Vaginal delivery rates within 12 hours were 25 of 57 (43.9) for concurrent treatment compared with 27/57 (47.4) (relative risk 0.9, 95 confidence interval 0.6-1.4, P = .85) for oxytocin only; median VAS was 8 (interquartile range IQR 2) compared with 8 (IQR 2), P = .38. Uterine hyperstimulation was 14% compared with 5.3%, P = .20; overall vaginal delivery rates were 59.6% compared with 64.9%, P = .70; and induction to vaginal delivery interval 9.7 hours compared with 9.4 hours P = .75 for concurrent treatment compared with oxytocin, respectively. There was no significant difference for any other outcome. CONCLUSION: Concurrent vaginal dinoprostone and intravenous oxytocin for labor induction of term PROM did not expedite delivery or improve patient satisfaction. CLINICAL TRIAL REGISTRATION: Current Controlled Trials, www.controlled-trials.com, ISRCTN74376345